Arsenic, lead and cadmium removal potential of Pteris multifida from contaminated water and soil. Issue 12 (15th October 2018) - Rahman, Farzana; Sugawara, Kazuki; Huang, Yi; Chien, Mei-Fang; Inoue, Chihiro
ABSTRACT: The main threats to the environment from heavy metals are associated with arsenic (As), lead (Pb) and cadmium (Cd). In this study, the potential of Pteris multifida for removing As, Pb and Cd from hydroponic solution and pot soil was evaluated for the first time. Short-term (5 day) experiments were conducted to assess phytofiltration efficiency of temperate zone fern P. multifida and to compare it with mostly studied tropical zone fern P. vittata. Within 5 days, P. multifida accumulated 33% of As(III), whereas P. vittata could not accumulate that most toxic arsenic species As(III) at all. Long-term hydroponic results showed that 90% of Pb, 50% of As and 36% of Cd were removed by P. multifida . Concentration of As in the frond (22 mg/kg dw) was comparatively higher than other parts of plant and significantly higher concentration of Cd and Pb were stored in root and rhizome. Pot soil experiment of P multifida confirmed the comparative uptake and translocation of As(V), Pb and Cd from soil. Therefore, from the assessment of heavy metal accumulation capacity, translocation and healthy survival for long time, P. multifida was identified as an excellent species for the treatment of multi-metal contaminated water and soil.